2010
DOI: 10.1007/s10875-010-9489-z
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular Diagnosis of Severe Combined Immunodeficiency—Identification of IL2RG, JAK3, IL7R, DCLRE1C, RAG1, and RAG2 Mutations in a Cohort of Chinese and Southeast Asian Children

Abstract: Severe combined immunodeficiencies (SCID) are a group of rare inherited disorders with profound defects in T cell and B cell immunity. From 2005 to 2010, our unit performed testing for IL2RG, JAK3, IL7R, RAG1, RAG2, DCLRE1C, LIG4, AK2, and ZAP70 mutations in 42 Chinese and Southeast Asian infants with SCID adopting a candidate gene approach, based on patient's gender, immune phenotype, and inheritance pattern. Mutations were identified in 26 patients, including IL2RG (n = 19), IL7R (n = 2), JAK3 (n = 2), RAG1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 41 publications
1
24
0
1
Order By: Relevance
“…Its database stores clinical information provided by the referring doctors, laboratory results, and genetic test reports (12–14). From 2005 to 2016, 147 SCID patients were referred from 23 centers to the APIN for consultation and genetic testing, 42 of whom were reported in our previous study (13). In our study, we included patients with documented age at presentation (AP) and diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its database stores clinical information provided by the referring doctors, laboratory results, and genetic test reports (12–14). From 2005 to 2016, 147 SCID patients were referred from 23 centers to the APIN for consultation and genetic testing, 42 of whom were reported in our previous study (13). In our study, we included patients with documented age at presentation (AP) and diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic analysis was performed in the Department of Pediatrics and Adolescent Medicine of the University of Hong Kong using PCR and direct sequencing (Table SE1 in Supplementary Material) (13). Genetic and functional studies on PID, data archival in the APIN database, and DNA storage were approved by the Clinical Research Ethics Review Board of the University of Hong Kong and Queen Mary Hospital (Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Several splice site prediction programs predict disruption of the exon 2 splice donor site due to the c.221+2T>G mutation (Table S1). Furthermore, a similar mutation (heterozygous c.221+2T>A) together with a heterozygous missense mutation in IL7R was found by Lee et al in a patient with T-B+ SCID [23]. Thus, compound heterozygosity for these variants could be considered causative.…”
Section: Resultsmentioning
confidence: 71%
“…Mutations in the X-linked IL2RG gene encoding γc causes more than 50 % of all SCID cases and mainly affects males; IL7R gene mutations result in at least 10 % of SCID cases and occur in both males and females (Buckley 2004). Previous studies have reported that certain unaffected people have missense homozygous IL7R gene mutations (Lee et al 2011). We suggest that in the case of our patient, X-SCID was not caused by an IL7R gene mutation, although CD127 expression in the patient was lower.…”
Section: Discussionmentioning
confidence: 99%